Cathepsin B expression in tumour cells and laminin distribution in pulmonary adenocarcinoma. - Higashiyama, M (1993)
AIMS: To determine the correlation between cathepsin B expression and laminin distribution in pulmonary adenocarcinoma tissue. METHODS: The distribution of cathepsin B and laminin was examined in 28 formalin fixed, paraffin wax embedded specimens of pulmonary adenocarcinoma tissue, using a double immunostaining technique with commercially available antibodies to cathepsin B and laminin, respectively. RESULTS: Tumour cells in 23 (82%) cases reacted to cathepsin B: 13 cases were weakly positive and 10 were strongly positive. Laminin in tumour associated basement membrane produced various staining patterns: two cases had an almost continuous distribution of laminin in tumour associated basement membrane in the tumour tissues, while a moderately discontinuous laminin distribution pattern was found in 12 cases, and a highly fragmented pattern was found in 14 cases. The degree of cathepsin B expression in tumour cells was significantly correlated with the break up of laminin staining. In some cases a discontinuous pattern of tumour associated laminin was frequently observed adjacent to cathepsin B positive tumour cell nests. CONCLUSIONS: Considering that cathepsin B has the capacity to degrade basement membrane components, including laminin, the inverse correlation shown in this study between the increase in cathepsin B expression by tumour cells and the diminution of laminin in tumour associated basement membrane could reflect local progression and spread by pulmonary adenocarcinoma.